Metadata, Digital Museum Spaces and Accessibility for Persons with Impairments - Jones, Kimberly (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2022)
This study examines the intersection of metadata and accessibility in the digital museum space. While virtual museums can remove physical barriers to heritage institutions, virtual spaces still have barriers for certain impairments. Work done in the field of digital libraries has shown that accessibility metadata can help to remove some of those barriers. This exploratory research project aims to provide understanding of the ways that metadata in virtual museum spaces is being used and how that metadata can improve accessibility in these spaces. How can universal design be best applied to metadata in digital museum catalogs and objects? What kinds of metadata in digital museum collections can potentially increase accessibility? Are museums currently including metadata that increases accessibility for people with disabilities and impairments? These questions were explored using a content-analysis approach applied to textual information collected from forty objects in four digital collections found on the publicly accessible webpages of Canadian institutions of cultural heritage.